Finding Effective and Efficient Ways to Integrate Research Advances Into the Clinical Suicide Risk Assessment Interview - Rudd, M. David; Bryan, Craig J. (Frontiers in Psychiatry, 2022)
Research in clinical suicidology continues to rapidly expand, much of it with implications for day-to-day clinical practice. Clinicians routinely wrestle with how best to integrate recent advances into practice and how to do so in efficient and effective fashion. This article identifies five critical domains of recent research findings and offers examples of simple questions that can easily be integrated into a clinician’s existing suicide risk assessment interview and related protocol.